IMPLEMENTATION OF MANAGEMENT INFORMATION SYSTEMS TO IMPROVE THE EFFECTIVENESS OF DECISION MAKING - Khaira Amelia; Riska Mulfadillah; Rayyan Firdaus (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the impact of implementing Management Information Systems (MIS) on the effectiveness of decision making in various organizations. This study uses a mixed methods approach with a case study method. Data were collected through interviews, observations, surveys, and documentation. The results of the study indicate that implementing MIS increases the speed, efficiency, and accuracy of decision making. Analytical data generated by MIS also helps data-based decision making and risk management. However, MIS implementation also faces obstacles such as employee resistance and investment costs. The success of MIS implementation depends on organizational readiness, management support, and good change management.